Kekuatan Pembuktian Akta Risalah e-RUPS dalam Sistem eASY.KSEI ditinjau dari POJK Nomor 16/POJK.04/2020 - Angelia Mariani Santoso; Tjhong Sendrawan (Faculty of Law, University of Mataram, 2023)
Electronic shareholders’ meetings in Indonesia were allowed by article 77 paragraph (2) Law 40/2007 and for public company was regulated by OJK Regulation No. 16/POJK.04/2020. E-Shareholders’ meetings could be held using eASY.KSEI. The minutes must be made by Notary in the form of Relaas deed. The Notary must see, hear, and witness the shareholders’ meetings live. Regardless, the regular shareholders’ meeting still has to be held, unless there are special condition, which was attended by Notary while majority of the shareholders attended the meeting virtually. If there is no regular shareholders’ meeting, Notary will attend virtually. Law 2/2014 explained that “in front of the Notary” means physically, not virtually. Law 40/2007 stated that the minutes must be signed by all shareholders. Meanwhile, the sign was not required in OJK 16/2020. This conflict between two regulations might cause confusion in Notary’s occupation to make the minutes. The issues to be discussed are regarding how Notary carries the occupation to make the e-Shareholders’ meeting’s minutes that was held using eASY.KSEI and regarding the position and strength of evidence of the minutes. The research method used is doctrinal legal research with analytical explanatory as the research typology. Secondary data was used by literature study that analyzed with qualitative method. Based on the research, it was found that in emergency situation, Notary used OJK 16/2020 to make e-shareholders’ meeting’s minutes and the minutes qualifies as an authentic deed. Even though there are no articles that allowed “in front of” Notary virtually in Law 02/2014 and the minutes must be signed by all shareholders according to Law 40/2007, but using “lex spesialis derogat legi generali” principle, Notary should follow OJK regulations. However, since the “specialis” principle is OJK regulation, it is recommended that regulations be made as an act to have a stronger legal basis.